2016
DOI: 10.15386/cjmed-547
|View full text |Cite
|
Sign up to set email alerts
|

Risk and resilience factors of persons exposed to accidents

Abstract: Background and aimsResilience encompasses factors promoting effective functioning in the context of adversity. Data regarding resilience in the wake of accidental trauma is still scarce. The aim of the current study is to comparatively assess adaptive, life – promoting factors in persons exposed to motor vehicle accidents (MVA) vs. persons exposed to other types of accidents, and to identify psychological factors of resilience and vulnerability in this context of trauma exposure.MethodsWe assessed 93 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It was reported that providing stroke-related information and skills training could improve caregivers' resilience, which was considered a key construct to regulate future uncertainties ( 70 , 71 ). On the other hand, Hetra et al reported that coping with uncertainty was more likely to foster resilience after experiencing life-threatening accidents, such as a sudden stroke ( 72 ). The resilience enhancement program emphasized community integration among caregivers of people with stroke by seeking emotional support and providing psychoeducation and information.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that providing stroke-related information and skills training could improve caregivers' resilience, which was considered a key construct to regulate future uncertainties ( 70 , 71 ). On the other hand, Hetra et al reported that coping with uncertainty was more likely to foster resilience after experiencing life-threatening accidents, such as a sudden stroke ( 72 ). The resilience enhancement program emphasized community integration among caregivers of people with stroke by seeking emotional support and providing psychoeducation and information.…”
Section: Discussionmentioning
confidence: 99%